INCREASING BRAND AWARENESS AND IMPLEMENTING MARKETING MANAGEMENT STRATEGIES FOR DEPOK CITY MSMEs - Ridwan Taufik Hidayat; Lucky Anggara; Ratna Diah; Rossa Anjalina Soraya; Sri Henny Romauli Sitepu; Yayan Sudaryana; Zulfitra, Zulfitra (Bajang Institute, 2024)
In the era of globalization and digitalization, Micro, Small, and Medium Enterprises (MSMEs) face significant challenges in brand awareness and marketing management strategies, especially at the local level. This research focuses on MSMEs in Depok, aiming to analyze and identify effective strategies to enhance brand awareness and implement marketing management practices. The study employed both qualitative and quantitative approaches to collect and analyze data. The findings revealed that most MSMEs in Depok face difficulties in gaining brand recognition due to limited capital and knowledge of digital marketing. The training program on